Pengaruh Kepemimpinan, Motivasi Kerja, Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT Wilmar Nabati Teluk Bayur Padang - Narenda .; Marta Widian Sari; Yosi Puspita Sari (CV. ITTC INDONESIA, 2026)
This study aims to determine the influence of leadership and work motivation on employee performance, with job satisfaction as an intervening variable, among employees of PT Wilmar Nabati Teluk Bayur Padang. Data collection was conducted through a survey and questionnaire distribution with up to 80 respondents. The analysis method used was path analysis using the SmartPLS application. The results obtained based on partial tests showed a significant influence of leadership on job satisfaction. There was a significant influence of work motivation on job satisfaction. There was a significant influence of leadership on employee performance. There was an insignificant influence of work motivation on job satisfaction. There was a significant influence of job satisfaction on employee performance. There was a significant influence of leadership on employee performance through job satisfaction as an intervening variable. There was a significant influence of work motivation on employee performance through job satisfaction as an intervening variable.